2014
DOI: 10.1194/jlr.p049064
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein subclasses and endogenous sex hormones in women at midlife

Abstract: This article is available online at http://www.jlr.org in lipoprotein profi le around the time of menopause, including increases in total cholesterol, triglycerides, ApoB, and LDL cholesterol (LDL-C) ( 1, 4-7 ), which suggest a possible role of endogenous sex hormones. The reduction in plasma estradiol (E2) level that accompanies the menopausal transition has been suggested as a possible mechanism for this alteration of lipid profi les. This hypothesis was supported by the favorable infl uence of hormone thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 38 publications
1
10
1
3
Order By: Relevance
“…Socioeconomic status is a foremost driver of race/ethnic health disparities, and a major determinant of behavioral and clinical risk factors, including smoking and other lifestyle habits, obesity, and diabetes 24,31 . In a combined analysis of two prospective registries, low socioeconomic status had the strongest association with mortality postacute MI independent of race, as compared with other risk factors 32 . Apart from lower socioeconomic status, it is well documented that female adolescents have an increased risk of glycemic dysregulation as compared with their male counterparts, although in our study, significant differences were seen in the middle‐aged, but not young age group 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic status is a foremost driver of race/ethnic health disparities, and a major determinant of behavioral and clinical risk factors, including smoking and other lifestyle habits, obesity, and diabetes 24,31 . In a combined analysis of two prospective registries, low socioeconomic status had the strongest association with mortality postacute MI independent of race, as compared with other risk factors 32 . Apart from lower socioeconomic status, it is well documented that female adolescents have an increased risk of glycemic dysregulation as compared with their male counterparts, although in our study, significant differences were seen in the middle‐aged, but not young age group 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Возможно, различия между мужчинами и женщинами в действии статинов на субфракционный спектр ЛПНП связаны с гормональным статусом. Действительно, было показано, что половые гормоны влияют на суфракционный спектр ЛПНП [13][14]. Разный эффект статинов может быть обусловлен не только гормональным статусом, но и меньшей приверженностью женщин к лечению статинами.…”
Section: Discussionunclassified
“…По данным одних исследователей статины более эффективны у мужчин, по данным других -у женщин [10][11][12]. Разный эффект статинов у мужчин и женщин объясняют гормональным статусом, меньшей приверженностью женщин к лечению этими препаратами, разными дозами [13][14].…”
Section: Subfraction Distribution Of Apo B-containing Lipoproteins суunclassified
“…It encompasses the menopausal transition, a pivotal marker in women's aging process, when several hormonal and biological changes take place (11). Evidence showed that women are vulnerable to body fat redistribution, vascular remodeling, and physical functioning changes at midlife (12)(13)(14), with the menopausal transition and its related hormonal changes were found to contribute to this vulnerability (15). Given the coincidence increase risk of fat redistribution, vascular remodeling and physical functioning changes in women at midlife, evaluating a potential link between midlife PVAT and physical functioning status later in life is critical for women.…”
mentioning
confidence: 99%